2016
DOI: 10.1038/srep21300
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Forces Cause the Nucleus to Deform in a Highly Controlled Anisotropic Manner

Abstract: Physical forces arising in the extra-cellular environment have a profound impact on cell fate and gene regulation; however the underlying biophysical mechanisms that control this sensitivity remain elusive. It is hypothesized that gene expression may be influenced by the physical deformation of the nucleus in response to force. Here, using 3T3s as a model, we demonstrate that extra-cellular forces cause cell nuclei to rapidly deform (<1 s) preferentially along their shorter nuclear axis, in an anisotropic mann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 57 publications
8
87
0
Order By: Relevance
“…Interestingly, hMSC nuclei were strained along their minor axes, while the major axes maintained the same length in all levels of confinement. This is in agreeance with previous work, which showed that nuclei from 10 different cell types deform in an anisotropic manner and preferentially deform along their minor axis when an active force is applied by an atomic force microscope tip (Haase et al, ). hMSCs herein experience a passive force while migrating through microchannels, suggesting that anisotropic nuclear deformation can result from both active and passive forces.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, hMSC nuclei were strained along their minor axes, while the major axes maintained the same length in all levels of confinement. This is in agreeance with previous work, which showed that nuclei from 10 different cell types deform in an anisotropic manner and preferentially deform along their minor axis when an active force is applied by an atomic force microscope tip (Haase et al, ). hMSCs herein experience a passive force while migrating through microchannels, suggesting that anisotropic nuclear deformation can result from both active and passive forces.…”
Section: Discussionsupporting
confidence: 93%
“…demonstrate, using isotropic and elongated cell geometries, a link between cell geometry and chromatin fluctuations where the interplay between active cytoskeletal forces and nuclear rigidity from lamin A/C together regulate nuclear and chromatin dynamics 62 . Anisotropic nuclear deformation in response to extracellular forces is also regulated by the interplay between cytoskeletal tension, and nuclear architecture including both chromatin and lamin A/C organization 117 . Together, these studies demonstrate that with alteration of nuclear-cytoskeletal connectivity and mechanics, it is possible for a cell to change the site where a given mechanical stimulus achieves its effect to tailor the mechano-response.…”
Section: Interplay Between Nuclear and Cytoplasmic Mechanotransductionmentioning
confidence: 98%
“…Polymers of actin, tubulin, and vimentin appear to have unique roles in maintaining nuclear shape when cells are exposed to different forces of varying magnitudes 11,19,36,37 . In epithelial cells, the anchoring of microtubule (MT) minus-ends at cell-cell adhesion complexes results in the stabilization, nucleation, and polymerization of MTs along the apicobasal axis [38][39][40][41][42] , and the 4 capture of plus-end MTs by nuclear bound SYNE-4, a scaffolding protein that is part of SUN-KASH complexes which interact with plus-end directed Kinesin-1 MT-bound motors 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In some cancer cells, a highly deformable nucleus is necessary to squeeze through small pores (<10 microns) in 3D environments during confined migration 31,32 . Dysregulation in nuclear morphogenesis is also linked to genome instability 33 , alterations in the dynamics of DNA damage repair 4,34,35 , and the activation of proinflammatory pathways 24, 27 -all of which can contribute to tumorigenesis and metastasis.Polymers of actin, tubulin, and vimentin appear to have unique roles in maintaining nuclear shape when cells are exposed to different forces of varying magnitudes 11,19,36,37 . In epithelial cells, the anchoring of microtubule (MT) minus-ends at cell-cell adhesion complexes results in the stabilization, nucleation, and polymerization of MTs along the apicobasal axis [38][39][40][41][42] , and the 4 capture of plus-end MTs by nuclear bound SYNE-4, a scaffolding protein that is part of SUN-KASH complexes which interact with plus-end directed Kinesin-1 MT-bound motors 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation